2020
DOI: 10.1093/jamia/ocaa102
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of big data analytics for clinical decision-making: a scoping review

Abstract: Abstract Objective Much has been invested in big data analytics to improve health and reduce costs. However, it is unknown whether these investments have achieved the desired goals. We performed a scoping review to determine the health and economic impact of big data analytics for clinical decision-making. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 99 publications
(126 reference statements)
0
17
0
Order By: Relevance
“…Bakker et al expressed that the terms "advanced", "best practice", or "traditional" are time-dependent. Therefore, the definition of big data should encompass a list of analytics that are regarded as advanced or best practice, which is time dependant and updated regularly (Bakker et al, 2020). Big data in healthcare needs to be assessed, updated, and interpreted periodically to ensure maximum output.…”
Section: Big Data and Predictive Analytics In Healthcarementioning
confidence: 99%
See 2 more Smart Citations
“…Bakker et al expressed that the terms "advanced", "best practice", or "traditional" are time-dependent. Therefore, the definition of big data should encompass a list of analytics that are regarded as advanced or best practice, which is time dependant and updated regularly (Bakker et al, 2020). Big data in healthcare needs to be assessed, updated, and interpreted periodically to ensure maximum output.…”
Section: Big Data and Predictive Analytics In Healthcarementioning
confidence: 99%
“…This type of analytics can be used to predict outbreaks and epidemics, identify communities or individuals in need of health services, or predict load default or forecasting weather. The Chicago Department of Public Health used these analytics to develop microtargeting campaigns for mammography screening ( Bakker et al., 2020 ). Prescriptive Analytics: Prescriptive analytics help to undertake the best possible course of action based on information learned through descriptive and predictive analysis.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and See also performed a review published in the JMIR and found several similar limitations [ 135 ]. In July of 2020, Bakker et al from the Netherlands published a systematic review of the health and economic impact of big data analytics for clinical decision making (not specific to COVID-19) in the JAMIA [ 136 ]. They reviewed 12,311 papers for eligibility and found only seven papers that reported cost-savings and improved outcomes from implemented “big data analytics” models.…”
Section: Artificial Intelligence In Diagnosis and Predictive Analyticsmentioning
confidence: 99%
“…Future studies should also look into developing a proper sports economics' frameworks, inspired by health economics [42,127,151,569], which would include the time and nancial cost of given measurement technology compared to its expected value for athletic performance.…”
Section: Precision Strength Trainingmentioning
confidence: 99%